Prescribing pattern of proton pump inhibitors among patients visiting the outpatient general medicine clinic in a tertiary care teaching hospital in Nepal - Bijaya Basyal; Nirmal Raj Marasine; Sabina Sankhi; Rajendra Lamichhane; Bipashwi Nath Uprety (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - The purpose of this study is to evaluate the prescribing pattern of proton pump inhibitors (PPIs) in patients visiting the outpatient general medical clinic in a Tertiary Care Teaching Hospital. Design/methodology/approach - A hospital-based cross-sectional study was conducted in 419 patients aged ≥18 years, visiting the outpatient general medicine clinic of a tertiary hospital and prescribed with at least one PPI, from July to September 2016 using a purposive sampling technique. Descriptive statistics were performed using IBM-SPSS 20.0 (IBM Corporation, Armonk, NY, USA). Findings - Patients were mostly less than 30 years (30.78%) and female (58.95%). Pantoprazole was the most frequently prescribed PPIs (57.04%). The majority of PPIs were prescribed for acid peptic disorder (APD) (33.65%), followed by non-steroidal anti-inflammatory drugs (NSAIDs) prophylaxis (30.79%). Most of the PPIs were prescribed for twice-daily administration (68.26%). Nearly one-fourth (21.72%) of the patients presented with at least one additional medical condition, and almost all (99%) patients were receiving at least one additional drug along with PPIs. Originality/value - The study suggests that PPIs are frequently prescribed and their use has been extended to other conditions that in fact do not require acid anti-secretory therapy. Result has highlighted the need for an interdisciplinary collaboration between pharmacists and medical professionals for the rational use of PPIs and promotion of PPIs prescription from the National List of Essential Medicines.